2020
DOI: 10.1001/jamanetworkopen.2020.23256
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Disorders With Physician Burnout

Abstract: This cross-sectional study evaluates the association between sleep disorders and burnout symptoms among faculty and staff at a large teaching hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 6 publications
(10 reference statements)
4
19
0
1
Order By: Relevance
“…The relationship of sleep quality with psychological outcomes was also substantial. This relationship may be bidirectional as it is consistent with both the known deleterious effects of nonrestorative sleep on professional burnout [ 41 ] and the sleep-disrupting effects of common psychiatric illnesses. Education about sleep hygiene, as well as organizational attention to the impact of shift work and shift length on sleep may support resilience, although this requires further research since the direction of causality cannot be determined in the current study.…”
Section: Discussionmentioning
confidence: 75%
“…The relationship of sleep quality with psychological outcomes was also substantial. This relationship may be bidirectional as it is consistent with both the known deleterious effects of nonrestorative sleep on professional burnout [ 41 ] and the sleep-disrupting effects of common psychiatric illnesses. Education about sleep hygiene, as well as organizational attention to the impact of shift work and shift length on sleep may support resilience, although this requires further research since the direction of causality cannot be determined in the current study.…”
Section: Discussionmentioning
confidence: 75%
“…Finally, our study showed a significant association of burnout with substance abuse and taking medications for sleep disorders among dentists in Lithuania. Several studies have also confirmed the substantial link of burnout with illegal substance use [ 19 , 46 ] and taking medications for sleep disorders [ 21 , 47 ]. However, our study showed a substantial interaction between these lifestyle factors.…”
Section: Discussionmentioning
confidence: 98%
“…There is evidence that physical activity has a huge potential to enhance physical health and wellbeing [ 51 ], so it should be assumed that any kind of physical activity is a great way to prevent burnout [ 52 ]. It is likely that adequate sleep duration is also an important factor in reducing burnout [ 43 , 47 , 50 ]. In our study sleep in free time was associated with a lower DP sum score.…”
Section: Discussionmentioning
confidence: 99%
“…5 Sleep disorders are very common, with 30-40% of employees screening positive for at least one common sleep disorder. [6][7][8][9] Approximately 85% of those with sleep disorders are undiagnosed and untreated. 6,10 Screening positive for a sleep disorder has been associated with a myriad of adverse health consequences, including increased risk of cardiovascular disease, diabetes and depression.…”
Section: Introductionmentioning
confidence: 99%